James J. Dinsmore letter to Robert K. Myers regarding bird sightings, spring 1988 - Dinsmore, James J.et al (1988)
Field notes contributed by James J. Dinsmore in a letter to Robert K. Myers. The field notes include an attachment with additional birds observed by Erwin E. Klaas, Darryl Kroeker and Clayton Swanson. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1988. Epson - sheet feed